Recent Progress of Delivery Systems Based on Cyclodextrin and Its Derivatives in Food Industry - Yumiao SHEN; Qian WANG; Yu GUO; Jiaqi NIU; Mengmeng SUN (Shipin gongye ke-ji, 2022)
Taking advantages of nontoxicity and odorlessness, cyclodextrin and its derivatives can encapsulate some bioactive substances with poor water solubility and sensitivity to light, temperature, and pH, thus to enhance their aqueous solubility and stability, mask bad odor, and also targeted release them. This paper reviews recent researches on cyclodextrin-based delivery systems for carrying active substances. Firstly, several delivery systems based on cyclodextrin and its derivatives are introduced, including inclusion complexes, hydrogels, and Pickering emulsions. In this part, the advantages and drawbacks as well as the scope of applications of several common preparation methods of inclusion complex, i.e., coprecipitation method, ultrasonic method, grinding method, freeze-drying method and spray-drying method are detailed described and discussed. Then, the protection and delivery of cyclodextrin-based delivery systems to antibacterial agents, antioxidants, vitamins, proteins and other active ingredients in food industry are summarized. Finally, further research and application of cyclodextrin-based delivery systems in food industry are prospected, which would provide a theoretical basis for subsequent research.